Disciplinary Character Analysis of Post-Covid-19 Grade IV Elementary School Students: Analisis Karakter Disiplin Siswa Pasca Covid-19 Kelas 4 Sekolah Dasar - Firdaus, Gita Fadlilah; Supriyadi, Supriyadi (Indonesian Journal of Education Methods Development, 2023)
This study aims to analyze the disciplinary character of post-covid-19 students with objects at Lemahputro 1 Sidoarjo State Elementary School. The research approach uses qualitative research with the type of case study. The research subjects were 5 students and 1 class teacher. Subject selection is based on the consideration that the subject is the perpetrator who carries out the discipline. Collecting research data using the method of observation, interviews, and documentation. Then analyzed using the Miles model analysis technique with the stages of data reduction, data presentation, and drawing conclusions or data verification. The results of the study that the disciplined character of post-covid-19 elementary school students showed some indications that subjects still tended to be less disciplined in the habit of arriving on time when entering class, using attributes, paying less attention to when the teacher explained the material, collecting and doing assignments according to the specified time and lacking discipline. on the use of good and correct language rules. The disciplined character of post-covid-19 elementary school students can be seen in class picket activities, throwing trash in its place, and attending ceremonies